Limb salvage surgery in chronic osteomyelitis : a case report - Muhammad Hafiz AS,; Mohd Yazid Bajuri,; Norliyana M,; Rasyidah R, (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Osteomyelitis refers to an infection of the bone characterized by progressive inflammatory destruction caused by infecting microorganism. Open fracture carries the risk of developing osteomyelitis from 3 to 50% with a high amputation rate. Salvage of the limb is always a challenge and needs perseverance. We report the case of a 44-year-old male with chronic osteomyelitis with successful multiple limb salvage surgeries. The curative approach to chronic osteomyelitis has the following goals including arrest of infection, pain reduction and salvage of limb and function. With regard to survival and function, the result obtained in this case is more promising compared to above knee amputation.